Lung involvement in childhood onset granulomatosis with polyangiitis - Giovanni Filocamo; Sofia Torreggiani; Carlo Agostoni; Susanna Esposito (BMC, 2017)
Abstract Granulomatosis with polyangiitis is an ANCA-associated systemic vasculitis with a low incidence in the pediatric population. Lung involvement is a common manifestation in children affected by granulomatosis with polyangiitis, both at disease's onset and during flares. Its severity is variable, ranging from asymptomatic pulmonary lesions to dramatic life-threatening clinical presentations such as diffuse alveolar haemorrhage. Several radiologic findings have been described, but the most frequent abnormalities detected are nodular lesions and fixed infiltrates. Interstitial involvement, pleural disease and pulmonary embolism are less common. Histology may show necrotizing or granulomatous vasculitis of small arteries and veins of the lung, but since typical features may be patchy, the site for lung biopsy should be carefully chosen with the help of imaging techniques such as computed tomography. Bronchoalveolar lavage is helpful to confirm the diagnosis of alveolar haemorrhage. Pulmonary function tests are frequently altered, showing a reduction in the diffusion capacity for carbon monoxide, which can be associated with obstructive abnormalities related to airway stenosis. Nodular lung lesions tend to regress with immunosuppressive therapy, but lung disease may also require second line treatments such as plasmapheresis. In cases of massive diffuse alveolar haemorrhage, ventilator support is crucial in the management of the patient.